Wonderful Digital Tourism Indonesia Dan Peran Revolusi Industri Dalam Menghadapi Era Ekonomi Digital 5.0 - Ina Heliany (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2019)
The rapid development of information technology in the past two decades has changed the various settings of human life. The appearance of the 5.0 industrial revolution in Japan had an impact in all fields, including in the tourism sector. This era was marked by the ease of access to information through digital media. In this regard, Indonesia also does not want to be defeated, but in Indonesia the new Industrial Revolution era in the Era 4.0. This is the reason for the emergence of the phenomenon of cultural shifts from manual systems to cyber and visual, as well as in the tourism sector, especially Indonesian tourists who are millennial generations.Therefore the government program after Indonesia's independence until now, continues to try to improve industrial development with various policies, especially the tourism industry which is a mainstay at this time. The research discusses whether the program used in order to improve the development of Indonesian tourism in the face of tourist destinations with the concept of "contemporary" through a digital approach and what is the role of tourism in facing the industrial revolution in the digital economy era.The research method used is a qualitative method. The results of the study were found to face current tourist destinations with 3 programs, namely Wonderful Startup Academy, Nomadic Digital Tourism and Destinations and the role of tourism in facing the digital era can be seen in marketing activities that can easily be accessed through internet media such as: websites, social media, online advertising, direct marketing e-mail, discussion forums and mobile applications. With the presence of digital marketing tourism, it is difficult to increase the country's foreign exchange earnings.